"E eu, anarquia, que sou tua filha fiel e dedicada estou de braços abertos para receber": mulheres no Movimento Anarquista do Rio Grande do Sul (1889-1930) - Schneider, Nicole Angélica (2022)
This dissertation has the objective of perceiving how working women were perceived in anarchist newspapers and other materials of ideological dissemination, understanding the discourses, as well as locating the workers and women who had anarchist actions in the labor movement in Rio Grande do Sul, who contributed in some way in the construction of strikes and anarchist awareness with the working class. The historiography on the World of Work in the First Republic is extensive, many researches have unveiled the organizations and faces that made up the movement that caused historic strikes, which at times were connected to international demands. With recent industrialization, European immigration, and the abolition of slavery, life in Rio Grande do Sul was changing and workers needed to adapt to the new rules and services. It was not long before ideas of labor organization, social transformation, and improvements to the lives of these workers began to circulate among the popular sectors. Among these ideas is anarchism. Through the method of direct action, dissemination through newspapers and plays, connection with other movements, union action, the search for liberation, education, and emancipation of workers from the evils caused by the system that was swallowing them up, anarchist ideas began to infiltrate among the working men and women.With these proposals to destroy the capitalist system, the anarchists formed a movement that was articulated among the workers and was involved in strikes and confrontations with brigadiers. Historiography presents a working class with a heterogeneous identity, composed of men, women, immigrants, blacks, and children, and this work is committed to contributing to this historiographical conception.